#### Answer

x = 0.75

#### Work Step by Step

Simplifying
-4x + 2 = 8x + -7
Reorder the terms:
2 + -4x = 8x + -7
Reorder the terms:
2 + -4x = -7 + 8x
Solving
2 + -4x = -7 + 8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8x' to each side of the equation.
2 + -4x + -8x = -7 + 8x + -8x
Combine like terms: -4x + -8x = -12x
2 + -12x = -7 + 8x + -8x
Combine like terms: 8x + -8x = 0
2 + -12x = -7 + 0
2 + -12x = -7
Add '-2' to each side of the equation.
2 + -2 + -12x = -7 + -2
Combine like terms: 2 + -2 = 0
0 + -12x = -7 + -2
-12x = -7 + -2
Combine like terms: -7 + -2 = -9
-12x = -9
Divide each side by '-12'.
x = 0.75
Simplifying
x = 0.75